How Safe Are Recently FDA‐Approved Antimicrobials? A Review of the FDA Adverse Event Reporting System Database. Issue 12 (25th November 2014) - Khadem, Tina M.; van Manen, Robbert P.; Brown, Jack
<x xml:space="preserve">Abstract</x> Study Objective To review quantitatively and qualitatively the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (AERS) database to provide clinicians with a general understanding of the comparative occurrence of clinically meaningful adverse events associated with 15 antimicrobial new molecular entities approved by the FDA since 2006: anidulafungin, darunavir, maraviroc, raltegravir, doripenem, telavancin, ceftaroline, boceprevir, telaprevir, fidaxomicin, bedaquiline, dolutegravir, simeprevir, sofosbuvir, and dalbavancin. Design Retrospective analysis. Data Source FDA AERS database. Measurements and Main Results Empirica Signal software was used to query the AERS database from November 1968 to December 2012. Using disproportionality analyses, we calculated a relative reporting ratio (RRR) estimate for reports of antimicrobial adverse events. The RRR estimate compares the occurrence of a specific adverse event with an index drug of interest to the occurrence of the same adverse event with similar agents or with all other FDA‐approved prescription drugs. Common industry practice considers an RRR meaningful if the 5th percentile of the distribution is at least 2 (RRR05 of 2.0 or higher). Antimicrobials were compared with agents within their respective antimicrobial therapeutic class as well as with all agents in the AERS database. Seventeen adverse signals with an RRR05 of 2.0 or higher were identified from the database for six agents. Ten of the 17 signals were not included in the most up‐to‐date manufacturers' package inserts for four of the six agents: doripenem‐associated hepatic dysfunction (RRR05 3.7) and hyperchloremia (RRR05 2.6); boceprevir‐associated weight loss (RRR05 2.2); darunavir‐associated premature labor (RRR05 3.1), sudden infant death syndrome (RRR05 2.9), ventricular hypertrophy (RRR05 2.7), acute coronary syndrome (RRR05 2.4), and congenital anomaly in offspring (RRR05 2.4); and raltegravir‐associated congenital heart valve disorders (RRR05 2.5) and SIDS (RRR05 2.3). Conclusion Clinically meaningful adverse event signals appeared to be associated with antimicrobial new molecular entities approved since 2006 including many not yet identified in package inserts. Although a disproportionality analysis suggests a quantitative signal for these associations, causality cannot be inferred from the data. Due to several key limitations in this type of analysis, investigative studies are needed to further explore these adverse event signals and the potential mechanisms by which they occur.